Peningkatan jiwa entrepreneurship bagi siswa SMK - Budiyati, Eni (University of Islam Malang, 2021)
The productive unemployment rate in Central Java is quite high, of which 13.5% are vocational graduates. Entrepreneurship can be a solution to reduce productive unemployment. However, to run entrepreneurship requires strong interest and motivation. This community service is carried out to increase the entrepreneurial spirit of students at SMK Muhammadiyah 4 Surakarta. The implementation stages include analysis of partner problems, data collection, presentation and training, filling out post-socialization questionnaires, and evaluating the results of the implementation. Tips and tricks, challenges and obstacles, the importance of motivation in entrepreneurship are the main material presented in the presentation. In the training, students make business plans based on their individual choices. The percentage of consideration in the business field choosing is dominated by the suitability of majors in SMK (about 40%) and the trend that is developing (20%). While, the reasons for the suitability of hobbies, family background and others are 18%, 14%, and 8%, respectively. The students' understanding and interest in entrepreneurship increased significantly. This increase can be seen from the change in the percentage of students' plans after graduation. The number of students who wish to work in agencies or companies is around 70% (before socialization) and about 30% (after socialization). The number of students interested in entrepreneurship increased from 15% to 68%. These results show that the students' interest has shifted from